Tau protein as a biomarker for asphyxia: a possible forensic tool? - Salama, Mohamed; Mohamed, Wael Mohamed Yousef (Elsevier, 2016)
Asphyxial death has been a problem for forensic investigations due to the absence of a validated biomarker for the diagnosis of this event. Recently, research on brain affection by asphyxia raised hopes on the possible use of CNSmarkers for asphyxia. The cytoskeletal proteins seemto be attractive targets as they are vulnerable to hypoxia and can be affected in asphyxial deaths. Tau, an important cytoskeletal protein, showed affection in many neurodegenerative disorders and recently in some acute incidences like trauma and brain ischemia. In this report we showthe affection of the normal pattern of tau and pathological aggregates of tau in the case of brain hypoxia. This may give new clues to asphyxial death investigations.